63‐1: High Transmittance and Fast Response Time Liquid Crystal Displays Using A Novel Electrode Pattern. Issue 1 (May 2016) - Ling, Ankai; Chen, Jianqun; Wu, Ling; Xie, Huimin; Shen, Poping; Tseng, Changho
Abstract : A method for enhancing the transmittance and response time of negative LC‐based fringing‐field switching (n‐FFS) liquid crystal displays (LCDs) has been demonstrated by using a new pixel electrode pattern. Compared to the conventional device, transmittance was enhanced extraordinarily by about 9.3% for 538 ppi and maximal gray to gray (GTG) response time was decreased enormously 6 ms.